A study exploring the autism awareness of first grade nursing and medical students in Istanbul, Turkey - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2016)
Objective: To assess the level of awareness about childhood autism among first-grade nursing and medical students. Methods: The descriptive study was conducted at Marmara University, Istanbul, Turkey, in December 2012, and comprised first-grade nursing and medical students. Data was collected using a self-administered questionnaire. Association between categorical variables was determined and p<0.05 was considered statistically significant. Results: Of the 175 students, 138(78.9%) were aware of autism, 14(8%) of them being highly aware and 124(70.9%) moderately aware, whereas 37(21.1%) were not aware. There was a significant difference in the awareness level as far as gender was concerned as 102(82.9%) females and 36(69.2%) males were aware (p=0.043). Moreover, 104(59.4%) participants were aware that autism was a neurodevelopmental disorder, 62(67.4%) of them being nursing and 42(50.6%) being medical students (p<0.05). Conclusion: First-grade medical and nursing students could be considered relatively well aware of autism as their awareness level was in between that of the general public and healthcare professionals.
Keywords: Autism; Awareness; Nursing students; Medical students; CHILDHOOD AUTISM; KNOWLEDGE; ATTITUDES